PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK TERHADAP KETERAMPILAN TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SD - Sukmawati; Irwan Akib; Mukhlis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to examine and describe the impact of the Realistic Mathematics Education (RME) approach on students' critical thinking skills, self-efficacy, and math learning outcomes. Conducted with fifth-grade students at UPT SPF SD Inpres Bontoa, the research employs a quantitative quasi-experimental method with a nonequivalent control group design. The sample, selected through simple random sampling, includes 61 students—32 in the experimental group and 29 in the control group. Data were collected via tests and questionnaires, and analyzed using descriptive and inferential statistics. Results from the MANOVA test show a significant difference (p = 0.009 < 0.05) between students taught with the RME approach and those taught with conventional teacher-centered methods in terms of critical thinking skills, self-efficacy, and learning outcomes. Specifically, critical thinking skills (p = 0.008 < 0.05), self-efficacy (p = 0.005 < 0.05), and learning outcomes (p = 0.003 < 0.05) were all significantly better in the RME group compared to the conventional teaching group.